Rethinking Social Realism in Gopal Prasad Rimal’s Masan - Budhathoki, Mahendra Kumar (The Outlook: Journal of English Studies, 2021)
This paper exposes the issues of urban middle class society of Nepal during the late Rana period in Gopal Prasad Rimal’s play Masan (Cremation Ground). The use of social realism in literature like in this play provides the actual social events and issues to expose within the same society and to other society. The research approach adopted includes social realism as a theoretical approach, textual analysis as a research method and note-taking as a research tool for verbal-data collection from the text. The findings provide evidence that the author portrays the real setting (Krishna’s ordinary room) of educated middle class actual family and social values of patriarchal society (Helen wishes bearing a child to run Krishna’s family line and open the heaven’s gate), real native tongue by the characters Krishna, Helen, Bhotu, Bride, maid of the play. This study explored tensions and struggles of man Krishna and woman Helen in real society; the exploitation of Helen’s body as a sex toy by preventing her bearing a child and the practice of polygamy are considered as social realistic issues in Nepali society. Helen determines to revolt against the sexist domination by separating her way from Krishna’s. The paper concludes that the author realistically portrays the reality of social life of Nepal before 2007B.S. in the play. This paper has shown the application of social realism in a Nepali play, and it presents how social realism theory can be applied in realistic literature, and understood the particular society.